Pemanfaatan Aplikasi Canva Untuk Meningkatkan Promosi Produk Usaha Mikro Kecil dan Menengah (UMKM) - Abdul Karim; Dwika Asrani (JPM: Jurnal Pengabdian Masyarakat, 2024)
Using the Canva application can increase promotion of MSME products through the ease of creating visual designs for promotional purposes. Canva provides various templates that can be used to promote MSMEs, including templates for culinary MSMEs. From the results of the activities carried out above, 25 students who took part in the activities were able to create good promotional media content and were able to apply Canva software on their respective participants' mobile phones.